Adenosine A2A Receptors Modulate Acute Injury and Neuroinflammation in Brain Ischemia - Felicita Pedata; Anna Maria Pugliese; Elisabetta Coppi; Ilaria Dettori; Giovanna Maraula; Lucrezia Cellai; Alessia Melani (Hindawi Limited, 2014)
The extracellular concentration of adenosine in the brain increases dramatically during ischemia. Adenosine A2A receptor is expressed in neurons and glial cells and in inflammatory cells (lymphocytes and granulocytes). Recently, adenosine A2A receptor emerged as a potential therapeutic attractive target in ischemia. Ischemia is a multifactorial pathology characterized by different events evolving in the time. After ischemia the early massive increase of extracellular glutamate is followed by activation of resident immune cells, that is, microglia, and production or activation of inflammation mediators. Proinflammatory cytokines, which upregulate cell adhesion molecules, exert an important role in promoting recruitment of leukocytes that in turn promote expansion of the inflammatory response in ischemic tissue. Protracted neuroinflammation is now recognized as the predominant mechanism of secondary brain injury progression. A2A receptors present on central cells and on blood cells account for important effects depending on the time-related evolution of the pathological condition. Evidence suggests that A2A receptor antagonists provide early protection via centrally mediated control of excessive excitotoxicity, while A2A receptor agonists provide protracted protection by controlling massive blood cell infiltration in the hours and days after ischemia. Focus on inflammatory responses provides for adenosine A2A receptor agonists a wide therapeutic time-window of hours and even days after stroke.